Dynamic Analysis of Internal Flow Field of Double-rectangular Cavity Hydrostatic Thrust Bearing - Zhang Yanqin; Quan Zhen; Feng Ya’nan; Kong Pengrui; Sun Jichang; Kong Xiangbin (Jixie chuandong)
Taking the Q1-205 type double-rectangular cavity hydrostatic thrust bearing as study object,the method combining theoretical analysis,dynamic simulation and experimental testing is used,aiming at the variation of oil film thickness under six inlet velocity and three working speed conditions,the velocity field,vorticity and pressure field are analyzed. Though the dynamic mesh technique,the relationship curves between the film thickness and the flow rate,vorticity and pressure of the film under different operating conditions are obtained. Which revealed the dynamic change rule of film performance. The results show that the low speed regions and high vorticity regions in the oil cavity are located at the edge seal of the countercurrent side,and the phenomenon increases with the decrease of film thickness. In the wake of the inlet velocity and pressure of oil cavity raise the pressure in the cavity reduces with the increase of working speed due to the serious pressure loss.